Study on the Manipulation Strategy of Metallic Microstructures Based on Electrochemical-Assisted Method - Dongjie Li; Mingrui Wang; Weibin Rong; Liu Yang; Donghao Xu; Yu Zhang (Micromachines, 2022)
Microcomponent manipulation (MCM) technology plays a decisive role in assembling complex systems at the micro- and nanoscale. However, the existing micromanipulation methods are difficult to widely apply in the manufacturing of microelectromechanical systems (MEMSs) due to the limited manipulation space and complex application objects, and the manipulation efficiency is relatively low, which makes it difficult to industrialize these micromanipulating systems. To solve the above problems, this paper proposes an efficient metal MCM strategy based on the electrochemical method. To verify the feasibility and repeatability of the strategy, the finite element model (FEM) incorporating the hydrodynamic and electrochemical theories is used to calculate the local stress distribution of the contact position during the dynamic pick-up process. Based on the simulation results, we defined the relationship between the parameters, such as the optimal manipulating position and angle for picking, transferring and releasing. The failure behaviors of pick-up are built to realize the efficient three-dimensional manipulation of microcopper wire of 300 μm. By establishing a theoretical model and experimental verification, it was concluded that the middle point was the best manipulating position when picking up the microcopper wire, the most efficient picking angle was between 45 and 60 degrees for the pipette, and the average time was 480 s in three sets of picking–release manipulation experiments. This paper provides an achievable idea for different types of micro-object manipulations and promotes the rapid application of micromanipulation techniques in MEMSs.